Strategi Pengurangan Emisi Gas Rumah Kaca dari Pengolahan Limbah Cair Industri Pulp Secara Aerob: Studi Kasus di Perusahaan X - Zurfi, Alfian; Desi Wiwin Sibarani (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The pulp industry is one of the sectors contributing to climate change, especially through greenhouse gas (GHG) emissions from wastewater treatment. This study aims to estimate the GHG emissions from the aerobic wastewater treatment applied by PT X using the IPCC method and to calculate the potential emission reduction by implementing anaerobic treatment. The results show that the COD concentration of the pulp industry effluent ranges from 500 to 600 mg/L. GHG emissions in the form of CH₄ are considered to be zero since the aerobic process does not produce CH₄, while CO₂ emissions from electricity consumption for the activated sludge aerator are 9.48 tons of CO₂/day. The implementation of anaerobic treatment is proposed as a solution to reduce GHG emissions by reducing electricity consumption and sludge production. Anaerobic treatment also has the potential to produce biogas, which can be used as an energy source for pulp production activities. The potential electrical energy from biogas utilization is estimated to be between 14.88 and 24.34 MWh, which is significant in reducing dependence on non-renewable energy sources while also reducing GHG and air pollutant emissions.